It’s Time for Health Record Banking! - Shabo Shvo, A. (Methods of Information in Medicine, 2014)
This article is part of a Focus Theme of Methods of Information in Medicine on Health Record Banking. This Focus Theme aims at describing the Health Record Banking (HRB) paradigm, which offers an alternative constellation of health information exchange and integration through sustainability of health records over the lifetime of individuals by independent and trusted organizations.It also aims at describing various approaches to HRB and reporting on the state-of-the-art HRB through actual implementations and lessons learned, as described in articles of this Focus Theme.
Keywords: Health record banking; electronic health records; health information integration; health information fragmentation; case-based reasoning; health information systems; health records sustainability